Electric and Magnetic Recordings by Chieti CIEN Station During the Intense 2016–2017 Seismic Swarms in Central Italy - Fidani, Cristiano; Orsini, Massimo; Iezzi, Giovanni; Vicentini, Noemi; Stoppa, Francesco (Frontiers in Earth Science, 2020)
We monitored electric and magnetic fields synchronously and continuously in an Italian area prone to moderate-to-high magnitude seismic activity. Identifying and monitoring of potential precursors may contribute to risk mitigation. A decade after the Central Italy Electromagnetic Network started, nine strong shakes with magnitudes between 5.0 and 6.6 occurred in Central Italy between August 2016 and January 2017. The events produced a fault offset of up to 2.8 m along a NNW–SSE normal fault system, 75 km long and located NW of the fault system, which generated the destructive L’Aquila 2009 earthquake sequence. This paper describes the electric and magnetic variations in the extremely low frequency band recorded at the Chieti Station of the network. Meteorological and geomagnetic data were compared to the recordings of these electric and magnetic activities by statistical correlations. Werecorded several abrupt increases in electric and magnetic activities not simultaneous to the main seismic events and presumptively related to them. Electrical signals consist in discrete electric field oscillations between 50 and 200 Hz, with time lapses lasting between 3 and 45 minutes. In addition, magnetic signals consisting of magnetic field pulses with time lapses greater than 10 ms were recorded in the same time interval. Similar signals occurred during the 2009 L'Aquila, Central Italy, sequence. Days before each strong earthquake, both electric and magnetic phenomena increased in intensity and number. Two physical models are proposed to describe and interpret electric and magnetic signal events. A number of hypotheses about the origin of recorded electric and magnetic signals may fit coherently with electromagnetic theory and are discussed in the light of a consistent dataset.